A profile of the language and cognitive skills contributing to oral inferential comprehension in young children with developmental language disorder. Issue 6 (7th October 2018) - Dawes, Emily; Leitão, Suze; Claessen, Mary; Kane, Robert
Abstract: Background: Children with developmental language disorder (DLD) demonstrate poor oral inferential comprehension. Research investigating the skills that underpin oral inferential comprehension in young children with DLD is necessary in order to better understand and improve inferential comprehension in this population. Aims: To profile the language and cognitive skills that contribute to oral inferential comprehension in young children with DLD. Methods & Procedures: Seventy‐six children aged 5–6 years with a diagnosis of DLD were assessed on a wide range of language and cognitive measures. Oral inferential comprehension of narrative was the primary outcome measure. Outcomes & Results: Narrative macrostructure and microstructure, literal comprehension, vocabulary, phonological loop, and theory of mind were significant predictors of inferential comprehension in bivariate analyses. However, multivariate regression analysis indicated that only narrative retell macrostructure and theory of mind contributed a significant amount of unique variance to inferential comprehension. Conclusions & Implications: This study profiled the skills contributing to oral inferential comprehension in young children with DLD, to support the clinical and theoretical understanding of the ability in this population. The findings have implications for future intervention studies.